Ligand–Receptor Interactions Elucidate Sex-Specific Pathways in the Trajectory From Primordial Germ Cells to Gonia During Human Development - Overeem, Arend W. (Front Cell Dev Biol, 2021)
The human germ cell lineage originates from primordial germ cells (PGCs), which are specified at approximately the third week of development. Our understanding of the signaling pathways that control this event has significantly increased in recent years and that has enabled the generation of PGC-like cells (PGCLCs) from pluripotent stem cells in vitro. However, the signaling pathways that drive the transition of PGCs into gonia (prospermatogonia in males or premeiotic oogonia in females) remain unclear, and we are presently unable to mimic this step in vitro in the absence of gonadal tissue. Therefore, we have analyzed single-cell transcriptomics data of human fetal gonads to map the molecular interactions during the sex-specific transition from PGCs to gonia. The CellPhoneDB algorithm was used to identify significant ligand–receptor interactions between germ cells and their sex-specific neighboring gonadal somatic cells, focusing on four major signaling pathways WNT, NOTCH, TGFβ/BMP, and receptor tyrosine kinases (RTK). Subsequently, the expression and intracellular localization of key effectors for these pathways were validated in human fetal gonads by immunostaining. This approach provided a systematic analysis of the signaling environment in developing human gonads and revealed sex-specific signaling pathways during human premeiotic germ cell development. This work serves as a foundation to understand the transition from PGCs to premeiotic oogonia or prospermatogonia and identifies sex-specific signaling pathways that are of interest in the step-by-step reconstitution of human gametogenesis in vitro.